Risk Factors for Intracardiac Thrombosis in the Right Atrium and Superior Vena Cava in Critically Ill Neonates who Required the Installation of a Central Venous Catheter - Alfredo Ulloa-Ricardez; Lizett Romero-Espinoza; María de Jesús Estrada-Loza; Héctor Jaime González-Cabello; Juan Carlos Núñez-Enríquez (Elsevier, 2016)
Central venous catheter (CVC) installation is essential for the treatment of critically ill neonates; however, it is associated with the development of neonatal intracardiac thrombosis, which is a complication that is associated with a poor prognosis. We aimed to identify specific risk factors for the development of intracardiac thrombosis in the right atrium (RA) and superior vena cava (SVC) related to the use of CVC in critically ill neonates. Methods: A case-control study was conducted at the tertiary referral neonatal intensive care unit of the Pediatric Hospital Siglo XXI in Mexico City, Mexico from 2008 to 2013. The included cases (n = 43) were de novo patients with intracardiac thrombosis in the RA and SVC diagnosed by echocardiography. The controls (n = 43) were neonates without intracardiac thrombosis or thrombosis at other sites. A logistic regression analysis was conducted, and odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results: The independent risk factors for intracardiac thrombosis in the RA and SVC were the surgical cut-down insertion technique (OR = 2.98; 95% CI: 1.18-9.10), a maternal history of gestational diabetes/diabetes mellitus (OR = 10.64; 95% CI: 1.13-121.41), Staphylococcus epidermidis infection (OR = 7.09; 95% CI: 1.09-45.92), and CVC placement in the SVC (OR = 5.77; 95% CI: 1.10-30.18). Conclusion: This study allowed us to identify several contributing factors to the development of intracardiac thrombosis in the RA and SVC related to the installation of a CVC in a subgroup of critically ill neonates. Multicenter and well-designed studies with a larger number of patients could help validate our findings and/or identify other risk factors that were not identified in the present study.